Measuring the quality of STAR websites using the System Usability Scale (SUS) method - Muhammad Labib Jundillah; Ramadiani Ramadiani; Azainil Azainil (Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the level of usability in the Learning Application System (STAR) at Mulawarman University using the System Usability Scale (SUS) method. Mulawarman University is a university in Indonesia located in Samarinda City and is currently trying to innovate in the educational aspect. Learning Application System (STAR) is a website designed to support the academic teaching and learning process at Mulawarman University. STAR Unmul can be accessed by lecturers and students. The existence of STAR Unmul which can be accessed via gadgets is very helpful for students in the lecture process. However, to ensure that the teaching and learning process runs optimally, STAR Unmul needs to be evaluated to determine how high the level of usability is in supporting the teaching and learning process at Mulawarman University